Music distraction - its efficacy in management of anxious pediatric dental patients - Marwah N; Prabhakar A; Raju O (Wolters Kluwer Medknow Publications, 2005)
Managing the anxiety of pediatric dental patient has long been the purview of dentists over many years. Various techniques have been used with moderate and variant success rates over the last few years. The main aim of this study was to ascertain if music distraction is an effective means of managing anxiety in pediatric dental patients. Forty children aged between 4 and 8 years were selected for the study. The assessment of anxiety was done using Venham′s picture test, Venham′s anxiety rating scale, pulse rate, and oxygen saturation during different treatment visits. The values were statistically analyzed and it was concluded that audio distraction did decrease the anxiety level in pediatric dental patients, but not to a very significant level.